Clinical and radiological characteristics of pulmonary actinomycosis mimicking lung malignancy - Baykal,Hüsnü (2022)
SUMMARY INTRODUCTION: Pulmonary actinomycosis, clinically and radiologically, mimics abscess, tuberculosis, and lung malignancy, resulting in misdiagnosis or delay in diagnosis. In this study, we analyzed the clinicoradiological features of pulmonary actinomycosis, the presence of any differences between clinical prediagnosis and radiological diagnosis, and whether imaging modalities help distinguish pulmonary actinomycosis from lung cancer. METHODS: A total of 22 patients who had a histopathological diagnosis of actinomycosis in a tertiary health center participated in this study. Of these, 14 had positron-emission tomography/computed tomography. RESULTS: In all, 81.8% of the patients were males. The diagnostic procedures employed for the diagnosis of actinomycosis were surgery in 54.5% of patients, fiberoptic bronchoscopy in 36.4% of patients, and rigid bronchoscopy in 9.1% of patients. Radiological and clinical prediagnosis showed malignancy in 31.8 and 40.9% of patients, respectively. The mean of the maximum standardized uptake value was 6.33±3.6 on positron-emission tomography/computed tomography. Kappa compliance analysis revealed that clinical and radiological diagnoses were significantly compatible with each other and that radiological pre-diagnoses were not superior to clinical diagnoses (κ=0.701 and p<0.001). CONCLUSION: Pulmonary actinomycosis shows high metabolic uptake in positron-emission tomography/computed tomography, and this may mislead clinicians for a diagnosis of malignancy. Our results suggest that positron-emission tomography/computed tomography does not help distinguish pulmonary actinomycosis from lung malignancy and does not provide a clear diagnostic benefit to the clinician, so pathological diagnosis is necessary.